1983
DOI: 10.1111/j.1365-2559.1983.tb02240.x
|View full text |Cite
|
Sign up to set email alerts
|

Oat cell carcinoma of the oesophagus: a clinico‐pathological study of 23 cases

Abstract: A review of 955 patients with primary oesophageal carcinoma treated with this hospital revealed 23 cases of small cell anaplastic carcinoma of the oat cell type. Fifteen were females and eight were males. In each case the histological appearances were identical to those of the oat cell carcinoma which is much more commonly encountered in the lung. In none of these cases was there any evidence of a primary oat cell carcinoma outside the oesophagus. Argyrophilic granules were seen in three cases and granules of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(38 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…This neoplasm has been reported in the esophagus [11,12,13,14,15], stomach [16,17,18,19,20,21], ampullary region [22], large bowel [23,24,25,26,27,28,29,30,31], and anorectal region [32,33]. …”
Section: Mixed Adenoneuroendocrine Carcinomas (Manecs)mentioning
confidence: 99%
See 1 more Smart Citation
“…This neoplasm has been reported in the esophagus [11,12,13,14,15], stomach [16,17,18,19,20,21], ampullary region [22], large bowel [23,24,25,26,27,28,29,30,31], and anorectal region [32,33]. …”
Section: Mixed Adenoneuroendocrine Carcinomas (Manecs)mentioning
confidence: 99%
“…The non-neuroendocrine component of high grade MANECs can be represented by tubulo-villous or villous adenoma [21,23,24,25,30,31], by adenocarcinoma [11,14,15,27,30,31,39,45] or, more rarely, by squamous cell carcinoma [11,12,15,31]. The squamous cell component is most often observed in esophageal and anorectal MANECs [11,12,15], whereas adenomatous or adenocarcinomatous areas are prevalently detected in gastric [17,19,21,35] and colorectal MANECs [15,23,24,25,30,31].…”
Section: Mixed Adenoneuroendocrine Carcinomas (Manecs)mentioning
confidence: 99%
“…9 It also remains a possibility that these tumors may be derived from a multipotential stem cell. [10][11][12][13] This hypothesis is supported by the findings of small-cell carcinoma combined with certain kinds of malignancy in various organs, such as squamous cell carcinoma or adenocarcinoma in the esophagus, 14,15 transitional cell carcinoma or adenocarcinoma in the urinary bladder, 12,16 adenocarcinoma in the colon and rectum, 17 and lobular carcinoma in the breast. 18 Although the origin of these types of malignant cells is obscure, the findings in our patient do not directly support the idea that small-cell carcinoma may arise from metaplastic epithelial cells, because the two types of tumors did not communicate with each other, and meta- plastic epithelial cells were not revealed in the microscopic findings.…”
Section: Discussionmentioning
confidence: 77%
“…Cytoplasmic argyrophilia is frequently noted but is not essential for making the diagnosis [12]. Briggs et al [20] reviewed 23 cases of esophageal small cell carcinoma and found argyrophilia in only 13%. Several authors have reported a mixed morphologic pattern with squamous cell carcinoma [1,4,5,8,15] or adenocarcinoma [4] intermingled with the small cell pattern.…”
Section: Discussionmentioning
confidence: 99%